Folic acid-mediated re-shuttling of ferritin receptor specificity towards a selective delivery of highly cytotoxic nickel(II) coordination compounds - Tesarova, Barbora; Charousova, Marketa; Dostalova, Simona; Bienko, Alina; Kopel, Pavel; Kruszyński, Rafał; Hynek, David; Michalek, Petr; Eckschlager, Tomas; Stiborova, Marie; Adam, Vojtech; Heger, Zbynek (International journal of biological macromolecules, 2019)
Metal-based coordination compounds, including the well-known cytostatic drug cisplatin, are widely used in the anticancer therapy. Generally, they exhibit high cytotoxicity not only towards malignant cells, but also towards non-malignant cells, which represents main problem of their clinical use. Herein, we describe the synthesis, characterization and biological testing of three trinuclear nickel(II) coordination compounds. Central nickel atoms are bridged by trithiocyanurate anion and coordinated by triamine and bis-benzimidazoles, respectively. To delineate a potential usage in anticancer therapy, we encapsulated the most cytotoxic complex into biomacromolecular protein cage apoferritin (FRT), forming FRTNi. FRT encapsulation markedly decreased the hemotoxicity of free Ni compounds. Despite FRTNi can be internalized through passive targeting by enhanced permeability and retention effect, we further introduced active targeting utilizing folate receptor (FR) via folic acid (FA)-modified FRT (FRTNiFA). Using breast cancer cell lines T-47D (FR+), MCF-7 (FR-) and non-malignant mammary gland derived cell line HBL-100 (FR-), we show pronounced FR-dependent internalization of FRTNiFA. Overall, we demonstrate that the FRT macromolecular nanocarrier provides a very low off-target toxicity, which could enable the use of highly toxic Ni compounds in cancer nanomedicine.
Keywords: Ligands; kyselina listová; Humans; buněčné klony; ligandy; komplexní sloučeniny; Folic Acid; buněčná smrt; Ferritins; ferritiny; lidé; Endocytosis; proliferace buněk; Coordination Complexes; receptory buněčného povrchu; endocytóza; apoptóza; Biocompatibility; Biocompatible Materials; nikl; Clone Cells; pohyb buněk; Receptors, Cell Surface; proteiny vázající železo; Cell Proliferation; Nickel; Iron-Binding Proteins; Cell Movement; nádorové buněčné linie; Cancer nanomedicine; biokompatibilní materiály; Cell Line, Tumor; Cell Death; Active targeting; Apoptosis